Keripik kaca: camilan renyah yang menginspirasi semangat berwirausaha - Qatrunnada, Salsabila Irbah (Maliki Interdisciplinary Journal, 2025)
Glass chips are snacks made from cassava that have undergone innovation in both appearance and flavor. The uniqueness lies in their transparent, glass-like appearance and crispy texture. This article explores the potential of glass chips as a creative business product that inspires youth entrepreneurship. By examining the success stories of Keripik Kaca entrepreneurs, this study highlights product adaptation strategies, digital marketing, and small-scale business management. The focus is on analyzing the socioeconomic impact of Keripik Kaca production and distribution on increasing household income and job creation. It is hoped that this study will provide valuable insights for aspiring entrepreneurs and policymakers in developing an inclusive and sustainable entrepreneurial ecosystem.